2013
DOI: 10.1890/12-1914.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in density dependence in age‐specific survival of a long‐distance migrant

Abstract: Density dependence in vital rates is key to population regulation. Rather than being constant, the strength of density dependence may vary throughout the year, but empirical evidence is limited. Based on 22 years of data of color-banded birds from a recovering population of Eurasian Spoonbills Platalea leucorodia leucorodia, we show, for the first time, seasonal variation in density dependence in survival of a long-distance migrating bird. Combining resightings and dead recoveries at breeding, stopover, and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 60 publications
4
32
2
1
Order By: Relevance
“…Dunlin are highly gregarious, particularly during winter, but this appears to come at some cost since juvenile survival decreased with increasing population size. (Saether et al 2000) and Eurasian Spoonbills Platalea leucorodia leucorodia (Lok et al 2013), indicating that competition for prey resources can be an important factor in regulating survival. The negative effects of increased conspecific density seen in this study imply that reduction in appropriate habitat and roost sites through disturbance and coastal squeeze could decrease survival of juvenile birds.…”
Section: Density Of Conspecificsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dunlin are highly gregarious, particularly during winter, but this appears to come at some cost since juvenile survival decreased with increasing population size. (Saether et al 2000) and Eurasian Spoonbills Platalea leucorodia leucorodia (Lok et al 2013), indicating that competition for prey resources can be an important factor in regulating survival. The negative effects of increased conspecific density seen in this study imply that reduction in appropriate habitat and roost sites through disturbance and coastal squeeze could decrease survival of juvenile birds.…”
Section: Density Of Conspecificsmentioning
confidence: 99%
“…Survival in other groups of species, including passerines and waterbirds, has also been observed to vary with population density on both the breeding and wintering grounds (Frederiksen and Bregnballe 2000, Lok et al 2013, Norman & Peach 2013. Competition for resources is likely to be the most important factor behind this density-dependent variation, particularly between less experienced foraging juveniles and more efficient adults; interaction with weather and predation have also been observed (Durell et al 2000, Frederiksen & Bregnballe 2000, Whitfield 2003, Tavecchia et al 2007.…”
mentioning
confidence: 99%
“…Most of the Spoonbills observed in Hungary were 1cy old, and very few were 2cy old. Spoonbills generally suffer large mortality during their first year of life (Pigniczki 2010, Lok 2013b and only a few immature Spoonbills return to their natal area, because most of them stay in the wintering ground or in proper wetlands between the wintering area and the natal area (Pigniczki 2015, Pigniczki & Végvári 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Spoonbills from the Wadden Sea area mainly follow the East Atlantic Flyway, and move to the Atlantic coast of France, Iberia or sub-Saharan Africa (Lok et al 2011(Lok et al , 2013a(Lok et al , 2013b, however, a few individuals were also observed in Tunisia (Smart et al 2007). A few Spoonbills of East Atlantic origin also reached continental Central Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation